ELECTRON DIFFRACTIONAN ALYSIS OF POLYCRYSTALLINE STRAIN-SENSITIVE FILMS (BIXSB1-X) 2TE3 (Scientific journal of the Fergana State University, 2023)
In this work, we studied the structure of the crystalline phases of the Bi ~ Sb-Te system obtained under various condensation conditions (the condensation rate W, the substrate temperature Tn), and the results of calculating interplanar distances from the data of the intensity of diffraction reflections.